Modern British and Irish criticism and theory : a critical guide - Wolfreys, Julian, 1958- (Edinburgh University Press, 2006)
A guide to the development of literary theory in Britain and Ireland, this book is aimed at advanced undergraduates, as well as academics working in the field. Beginning with Coleridge and Arnold, it contains essays that address the rise and significance of poetics, and literary and cultural studies. Each essay includes a further reading list.